2014
DOI: 10.1155/2014/621756
|View full text |Cite|
|
Sign up to set email alerts
|

Ameliorating Adriamycin‐Induced Chronic Kidney Disease in Rats by Orally Administrated Cardiotoxin from Naja naja atra Venom

Abstract: Previous studies reported the oral administration of Naja naja atra venom (NNAV) reduced adriamycin-induced chronic kidney damage. This study investigated the effects of intragastric administrated cardiotoxin from Naja naja atra venom on chronic kidney disease in rats. Wistar rats were injected with adriamycin (ADR; 6 mg/kg body weight) via the tail vein to induce chronic kidney disease. The cardiotoxin was administrated daily by intragastric injection at doses of 45, 90, and 180 μg/kg body weight until the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
6
14
0
Order By: Relevance
“…In particular, NTX could modulate T cell functions through modulating T cell division and cell cycle progression. During the study period, no death or any clinical manifestation of toxicity were observed in rats and mice administered with NNAV and NTX [25,50]. These findings highlighted the therapeutic potential of NNAV and NTX on the treatment of acute rejection following skin allograft and other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In particular, NTX could modulate T cell functions through modulating T cell division and cell cycle progression. During the study period, no death or any clinical manifestation of toxicity were observed in rats and mice administered with NNAV and NTX [25,50]. These findings highlighted the therapeutic potential of NNAV and NTX on the treatment of acute rejection following skin allograft and other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 63%
“…In the previous studies, we confirmed that oral administration of NNAV was effective in treatment of nephropathy [24], adjuvant arthritis [17] and systemic lupus erythematosus (SLE) [21]. NTX is relatively resistant to gastric protease degradation [17,24,25]. Thus we utilized oral administration of heat-treated NNAV and NTX in the present study.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Unfertilized eggs were fixed overnight at 4 °C in 4% [volume/volume (v/v)] formaldehyde and were embedded in paraffin and cut into 5‐μm sections. The yolk granule was detected by H&E staining (Ding et al ., ).…”
Section: Methodsmentioning
confidence: 97%